Identifikasi Capung Odonata pada Vegetasi Perairan, Rerumputan dan Tanaman Perdu di Kampus Indralaya Universitas Sriwijaya - Muthia A. Cendrawati; Tiara P. Rahmadhani; N. Meilita; Y. Pujiastuti (Seminar Nasional Lahan Suboptimal, 2018)
Cendrawati ete al, 2019. Identification of Dragonflies (Odonata) in Fresh Water, Grass and Herbaceous Vegetations in Indralaya Campus of Sriwijaya University. pp. 402-409.  Dragonflies (Odonata) play an important rule of the food chain. Dragonflies are effective predators in the ecosystem, play a role as natural enemies that can reduce the population of food crop pests. This indicates the important position of the existence of dragonflies in ecological balance. Dragonflies can also act as bioindicator in the ecosystem. Changes in dragonfly populations are a sign of the early stages of water pollution in addition to other signs in the form of water turbidity. This study aimed to determine the types and the behavior of Odonata on several traps in fresh water, grass and herbaceous vegetations in Indralaya Campus of Sriwijaya University. This research was conducted at the Unsri Indralaya Campus area, on December 2016. The study was arranged in a completely Randomized Completed Block Design (RCBD) consisted of two observation time, morning and afternoon, and 3 types of trap, unbranched trap (P1), two branched trap (P2), and three branched trap (P3) with 5 replications. Each branch was used as a trap which smeared by jackfruit sap. The results showed that unbranched trap (P1) on 3 different vegetations were preferred by dragonflies to perch and dragonflies in the Libellulidae family, namely Brachytemis contaminata were easy and most common found in each research location.